AN EVALUATION OF MICRO CREDIT SCHEMES OF SMALL AND MEDIUM ENTERPRISE DEVELOPMENT AUTHORITY (SMEDA) - S.S. Jaffar; K. Javed; T.E. Lodhi (Journal of Animal and Plant Sciences, 2006)
Small and Medium Enterprise Development Authority (SMEDA) claims to provide a nutritious jump to the small farmers for getting more produce from their farm. The present study was conducted to evaluate the project support services for agriculture credit of SMEDA in collaboration with Bank of Punjab (BOP). The purpose of the study was to assess the impact of micro credit scheme of SMEDA and BOP on crop productivity in two union council of district Sheikhupura of Punjab province. One hundred and twenty farmers from the selected villages were interviewed. The results indicated that majority of the farmers (76.7%) meet their financial requirements through institutional credit. More than 60% farmers obtained loans for fertilizers and about 50% got credit for quality seed where as about 37% for pesticides/insecticides etc. it was further indicated that all the farmers used the loan for the purpose for which it was obtained.
Keywords: SMEDA; micro credit; institutional credit; support services.